Analisis Dampak Estetika Situs Web, Aksesibilitas, Keamanan, dan Kecerdasan Buatan Terhadap Keputusan Pembelian di Era Digital - Anisa Nur Andina; Muliasari Pinilih (Jurnal Akuntansi, Manajemen dan Ekonomi, 2026)
The shift in consumer behavior from offline to online shopping requires sellers to consider several aspects for consumer comfort and an engaging experience. Consumers can easily navigate from one marketplace to another. Some aspects of consumer concern are website aesthetics, accessibility, security, and artificial intelligence support. Therefore, this study aims to analyze the influence of website aesthetics, accessibility, security, and artificial intelligence support on purchasing decisions. This study distributed questionnaires to 100 Purwokerto residents, and the data were analyzed using t-test and F-test approaches. The results showed that website aesthetics and accessibility did not influence purchasing decisions. However, security and artificial intelligence did influence purchasing decisions.